Modulation of mTOR Signaling in Cardiovascular Disease to Target Acute and Chronic Inflammation - Kaldirim, Madlen; Lang, Alexander; Pfeiler, Susanne; Fiegenbaum, Pia; Kelm, Malte; Bönner, Florian; Gerdes, Norbert (Frontiers in Cardiovascular Medicine, 2022)
Inflammation is a key component in the pathogenesis of cardiovascular diseases causing a significant burden of morbidity and mortality worldwide. Recent research shows that mammalian target of rapamycin (mTOR) signaling plays an important role in the general and inflammation-driven mechanisms that underpin cardiovascular disease. mTOR kinase acts prominently in signaling pathways that govern essential cellular activities including growth, proliferation, motility, energy consumption, and survival. Since the development of drugs targeting mTOR, there is proven efficacy in terms of survival benefit in cancer and allograft rejection. This review presents current information and concepts of mTOR activity in myocardial infarction and atherosclerosis, two important instances of cardiovascular illness involving acute and chronic inflammation. In experimental models, inhibition of mTOR signaling reduces myocardial infarct size, enhances functional remodeling, and lowers the overall burden of atheroma. Aside from the well-known effects of mTOR inhibition, which are suppression of growth and general metabolic activity, mTOR also impacts on specific leukocyte subpopulations and inflammatory processes. Inflammatory cell abundance is decreased due to lower migratory capacity, decreased production of chemoattractants and cytokines, and attenuated proliferation. In contrast to the generally suppressed growth signals, anti-inflammatory cell types such as regulatory T cells and reparative macrophages are enriched and activated, promoting resolution of inflammation and tissue regeneration. Nonetheless, given its involvement in the control of major cellular pathways and the maintenance of a functional immune response, modification of this system necessitates a balanced and time-limited approach. Overall, this review will focus on the advancements, prospects, and limits of regulating mTOR signaling in cardiovascular disease.